Stabilization of a twisted modulus on a mirror of rigid Calabi-Yau manifold - Keiya Ishiguro; Takafumi Kai; Hajime Otsuka (Journal of High Energy Physics)
Abstract We study the stabilization of a twisted modulus in Type IIB flux compactifications on a mirror of the rigid Calabi-Yau threefold. By analyzing the effective action of twisted and untwisted moduli, we find that three-form fluxes satisfying the tadpole cancellation conditions lead to supersymmetric AdS vacua. We also investigate swampland conjectures on this non-geometric background.